ANALYSIS OF INTERPRETING TYPES IN NCT'S SPECIAL AWARD VIDEO AT THE INDONESIAN TELEVISION AWARD - Pramudita Ariani; Nabilla Serly Adinda Putri; Ramadan Adianto Budiman (PT Akselerasi Karya Mandiri, 2023)
Language is a social communication tool as a sound symbol system resulting from human speech. Humans, as social beings, need means to interact with other humans in society. The number of languages in this world is an obstacle for some people to communicate. Someone who can help with communication problems is called an interpreter. An interpreter is someone skilled at translating language orally. This research aims to analyze the interpreting technique used by an interpreter in a YouTube video entitled